Kisah Cinta "Smaradahana" - Lestari, Nanny Sri (Wacana, Journal of the Humanities of Indonesia, 2004)
Kakawin Smaradahana is one of the most famaus literature in old Java. Untill these time Kakawin Smaradahana for Javanese people still give a great inspiration to write, so there is always a transformation from time to time. This short article shows how the manuscript transforms from time to time.